Differentially Methylated Loci Distinguish Ovarian Carcinoma Histological Types: Evaluation of a DNA Methylation Assay in FFPE Tissue. (24th September 2013) - Kelemen, Linda E.; Köbel, Martin; Chan, Angela; Taghaddos, Soreh; Dinu, Irina
Abstract : Epigenomic markers can identify tumor subtypes, but few platforms can accommodate formalin-fixed paraffin-embedded (FFPE) tumor tissue. We tested different amounts of bisulfite-converted (bs) DNA from six FFPE ovarian carcinomas (OC) of serous, endometrioid, and clear cell histologies and two HapMap constitutional genomes to evaluate the performance of the GoldenGate methylation assay. Methylation status at each 1, 505 CpG site was expressed as β -values. Comparing 400 ng versus 250 ng bsDNA, reproducibility of the assay ranged from Spearman r 2 = 0.41 to 0.90, indicating that β -values obtained with a lower DNA amount did not always correlate well with the higher amount. Average methylation for the six samples was higher using 250 ng ( β -value = 0.45, SD = 0.29 ) than with 400 ng ( β -value = 0.36, SD = 0.32 ). Reproducibility between duplicate HapMap samples (r 2 = 0.76 to 0.92) was also variable. Using 400 ng input bsDNA, THBS2 and ERG were differentially methylated across all histologic types and between endometrioid and clear cell types at <0.1% false discovery rate. Methylation did not always correlate with gene expression (r 2 = - 0.70 to 0.15). We found that lower bsDNA overestimates methylation, and, using higher bsDNA amounts, we confirmed a previous report of higher methylation of THBS2 in clear cell OC, which could provide new insight into biological pathways that distinguish OC histological types.